Сергій Іванович Руденко - учень Федора Вовка та вчитель Льва Гумільова (До 120-річчя від дня народження вченого) - Таран, О. (Народна творчість та етнографія, 2005)
This article is dedicated to work of Serhiy Ivanovych Rydenko - Ukrainian ethnographer, anthropologist, who was the student of Fedir Vovk and later the teacher of Lev Gumiliov. His work in the area of Skiffs Study brought him a great popularity in 1920th. In 1931 he was arrested and put behind bars for 3 years for counterrevolutionary propaganda. He was freed in 1934 but could fully renew his work only after the war. In 1957 he organized in Leningrad division of the Institute for History of Material Culture special laboratory for archeological technology and continued to be the head of the Ethnographical and Geographical Society until his death.